A marca do Batman: uma análise da presença simbólica do herói na mídia, imaginário e cotidiano da sociedade contemporânea de cultura pop. - Barbosa, Anderson Wagner da Silva (2017)
The representative figure of the mythological hero has an important significance for any and all society. Superheroes of comics have played a similar role in modern times not only because of their innumerable mediatic appearances, but because they are a direct or indirectly grounded form of representation in the heroic figure in the society of diverse cultures. In this scenario, Batman, hero of the comics, stands out in popularity and brings in one of the most well-known brands in pop culture and most valued of the cultural industry. However, in order to understand the representative strength of the character as a brand, it is necessary, first, to analyze the journey of the character, from its creation, to the media in which it is published, as well as the planned associations of Develop the narratives of the adventures of the hero, completely based on the concepts and mythical characteristics that form this type of character.